Perancangan Sistem Pajak BPHTB Berbasis Web Di PT. Mitra Prima Utama - Adil Syaifullah; Ahmad Rizal; Muhamad Derryanur; Aries Saifudin (CV. Multi Kreasi Media, 2022)
Abstract -In this era of globalization, all information needs must be met quickly and accurately. With the existence of web technology that is growing, it can make it easier to create an application that can provide fast and accurate information. The purpose of this activity is to optimize the Management of Collection of Regional Taxes / Regional Levies as regional revenue receipts can be realized through the availability of facilities and infrastructure that support good and easy administrative administration and service activities so that they are integrated, which are carried out by capable human resources and coordination of all work units involved in its management. This tax system is able to provide faster and realtime information so that it is able to complete the targets that have been charged